On the shoulders of hobbits : the road to virtue with Tolkien and Lewis - Markos, Louis (Chicago : Moody Publishers, 2012)
Introduces the classic virtues both good and bad through the stories of J.R.R. Tolkien and C.S. Lewis, and explains that real life truth and goodness are communicated powerfully through fantasy fiction.
The lure of the road -- Responding to the call -- Dangers on the road -- The end of the road -- The courage to endure -- Temperance and tobacco -- The wisdom that discerns -- The justice of the king -- Rehabilitating friendship -- The eyes of faith -- Hope and the happy ending -- The love that pities and forgives -- Forbidden fruit -- Perversion and corruption -- Blinded by the light -- Egyptian alliances.
Includes bibliographical references and index.
Keywords: Tolkien, J. R. R. -- 1892-1973 -- Criticism and interpretation; Lewis, C. S. -- 1898-1963 -- Criticism and interpretation; Christianity and literature